Targeting androgen receptor and WNT pathway in endocrine-resistant mammary carcinomas with high AR and low ER and PR levels - Figueroa, Virginia (2021)
Endocrine resistance remains a major drawback in the treatment of luminal breast cancer (BC). The mechanisms that contribute to hormone resistance may include deregulation of hormone receptors and growth factor signaling pathways.